Women in Public Space: Socio-cultural and Political Undertones in Sudraka’s Mrcchakatika - Singh, Jai (Literary Studies, 2021)
Any work of art directly or indirectly is a product of contemporary society. Sudraka’s Mrcchakatikais an amalgam of the extremely complex socio-cultural circumstances, economic relations of their society, and cross-cultural influences of Greek presence in India. This confluence of various forces is visible in Sudraka’s delineation of women characters especially Ganikas. Construction of woman persona i.e. Vasantasena is as per the theories of art and popular notions prevalent in those days however she does not conform to the tradition wholly, in many respects she challenges the accepted norm of the women prevalent in those days.